Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.6061/clinics/2021/e2189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the timing of laparoscopic cholecystectomy after endoscopic retrograde cholangiopancreatography on liver, bile, and inflammatory indices and cholecysto-choledocholithiasis patient prognoses

Abstract: Gao MJ, Jiang ZL. Effects of the timing of laparoscopic cholecystectomy after endoscopic retrograde cholangiopancreatography on liver, bile, and inflammatory indices and cholecysto-choledocholithiasis patient prognoses. Clinics (Sao Paulo).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…reported that performing LC within one to three days of ERCP was associated with a lower complication rate as compared with LC done four days or later. They also found that performing LC within one to three days of ERCP shortened the operative time ( 7 , 11 ). Borreca et al .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…reported that performing LC within one to three days of ERCP was associated with a lower complication rate as compared with LC done four days or later. They also found that performing LC within one to three days of ERCP shortened the operative time ( 7 , 11 ). Borreca et al .…”
Section: Discussionmentioning
confidence: 91%
“…and Gao et al . , operative time was significantly longer in patients receiving LC four days or later after ERCP ( 7 , 11 ). These results indicate that LC should be done within three days after ERCP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested that preoperative endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic extraction of CBDS might increase the risk of pancreatitis, cholecystitis, and cholangitis after treatment and cause inflammation around the CBD, which renders dissection of Calot's triangle to be more difficult. [19][20][21][22][23][24] Inflammation around the CBD could also lead to dysfunction of the sphincter of Oddi and could cause bacterial colonization into the bile duct and infection of the hepatoduodenal ligament. Some previous studies have reported that preoperative ERCP could be a strong predictor of conversion of LC to open surgery.…”
Section: Discussionmentioning
confidence: 99%